The Opportunity to Achieve Net Zero Emissions in Indonesia Through the Implementation of a Green Economy to Address Climate Change - Aulia Sabila Syarifa Qalbie; Rahmaniah Rahmaniah (Institute of International Studies, 2023)
This research discusses Indonesia's potential and challenges in implementing a green economy to achieve net zero emissions and address climate change. Global climate change poses a significant challenge to many countries, including Indonesia. To tackle this issue, implementing a green economy has been acknowledged as a practical approach to achieve substantial emission reductions and promote sustainable development. This research explores the potential of implementing a green economy in Indonesia to attain zero emissions and effectively address climate change. This research adopts a qualitative approach, utilizing a literature review, policy analysis, and case studies of green economy implementation in crucial sectors of the Indonesian economy. The analysis reveals that Indonesia possesses immense potential to adopt a green economy. However, several challenges hinder Indonesia's successful implementation of a green economy. This research provides valuable insights into Indonesia's potential, challenges, and efforts to achieve net zero Emissions. The Indonesian government has engaged in several collaborative partnerships involving various ministries of the Republic of Indonesia, domestic stakeholders, and international actors.Keywords: climate change; green economics; Indonesia; net zero emission